Evaluation of Application of Provisions of Business Accounting Standards and Law on Corporate Tax of the Republic of Lithuania - Štarolytė, Sandra (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian]The financial statements have to be prepared in accordance with Business Accounting Standards or International Accounting standards, but the data in the financial statements is still affected by the provisions of Lithuanian legislation. Although the Lithuanian legislation and business accounting standards have been harmonized since 2004, there are some differences which can cause an impact on the elements of financial statements. The biggest differences are noticed between the provisions of Business Accounting Standards and the Corporate Income Tax Law. Therefore, the purpose of this article is to determine the differences between the provisions of Business Accounting Standards and the Corporate Income Tax Law and their impact on the financial statements and decisions taken by the users of the financial statements. The following research methods are used: comparative analysis of scientific literature and information sources, synthesis, data collection and analysis, graphical data representation, statistical analysis, comparison, extrapolation, systematization. The article investigates the concept and meaning of financial and tax accounting; presents the methodology for the analysis of differences in the provisions of Business Accounting Standards and Corporate Income Tax Law; the evaluation of the results of the Business Accounting Standards and the Corporate Income Tax Law provisions’ application.The study revealed that the differences between the provisions of the Business Accounting Standards and the Corporate Income Tax Act affect both profitable and unprofitable enterprises. Comparing the effective corporate income tax rate with the fixed corporate income tax rate, it was found that in the majority of enterprises these figures do not match. The differences in the provisions of the Business Accounting Standards and Corporate Tax Law influenced the profitability indicators of 84.4% of enterprises. Therefore, the performed research revealed that there are differences between Business Accounting Standards and Corporate Income Tax Law provisions’ and they do the significant impact on financial statements and decisions taken by the users of financial statements.